Intracyclic variation of force and swimming performance - Morouço, P. G.; Barbosa, T. M.; Arellano, R.; Vilas-Boas, J. P. (International Journal of Sports Physiology and Performance, 2018)
Context: In front-crawl swimming, the upper limbs perform alternating movements with the aim of achieving a continuous application of force in the water, leading to lower intracyclic velocity variation (dv). This parameter has been identified as a crucial criterion for swimmers` evaluation. Purpose: To examine the assessment of intracyclic force variation (dF) and to analyze its relationship with dv and swimming performance. Methods: A total of 22 high-level male swimmers performed a maximal-effort 50-m front-crawl time trial and a 30-s maximal-effort fully tethered swimming test, which were randomly assigned. Instantaneous velocity was obtained by a speedometer and force by a strain-gauge system. Results: Similarity was observed between the tests, with dF attaining much higher magnitudes than dv (P<.001; d=8.89). There were no differences in stroke rate or in physiological responses between tethered and free swimming, with a high level of agreement for the stroke rate and blood lactate increase. Swimming velocity presented a strong negative linear relationship with dF (r=-.826, P<.001) and a moderate negative nonlinear relationship with dv (r=.734, P<.01). With the addition of the maximum impulse to dF, multiple-regression analysis explained 83% of the free-swimming performance. Conclusions: Assessing dF is a promising approach for evaluating a swimmer`s performance. From the experiments, this new parameter showed that swimmers with higher dF also present higher dv, leading to a decrease in performance.